Integrated management of Sorkhroud coastal area in line with tourism development - mehdi razjouyan; sadredin motevali; gholamrza janbaz ghobadi (تحقیقات کاربردی علوم جغرافیایی)
In the city of Sarkrood, the expansion of tourism trends with inappropriate planning and weakness of infrastructure and tourism management has had many negative effects on environmental, economic and social terms. The purpose of the present study is to integrate the Sarkhoud coastal area with a tourism development approach. The research is a descriptive-analytical, and the method of collecting research data on the theoretical foundations of research, recognition and analysis of Data and Libraries is in relation to field studies in relation to the study sample. The questionnaire tool has been used to collect field information, which has been distributed among the random sample of 20 people. Exoert choice software has been used to analyze the questionnaire data. The AHP hierarchical analysis method has been used for weightlifting and ranking criteria. The questionnaires were also distributed among experts and citizens to investigate the relationship between tourism and economic and environmental components, and the findings were analyzed using the Tau Kendall B and Pearson correlation test. The results show that from the point of view of half of government officials and experts, the expansion of the tourism industry on the one hand reduces the region's economic prosperity and on the other hand reduces regional security and environmental pollution. So in the current situation there is no motivation to expand the tourism industry for government managers; Thus, in order to prevent gaps and parallel activities, the provision of services to sustainable tourism development requires the integration of tourism management and continuous planning in organized, participatory and popular.